Topical diagnosis of diseases of the nervous system: textbook for students of English-language faculties of medical universities, clinical residents and neurologistsТопическая диагностика заболеваний нервной системы: учебник для использования в образовательном процессе образовательных организаций, реализующих программы высшего образования по специальностям 31.05.01 "Лечебное дело", 31.05.02 "Педиатрия", 31.05.03 "Стоматология" - Карпов, С. М. неврология Сергей Михайлович (Textbook, 2018)
The textbook is devoted to the issues of topical diagnostics in neurology. It presents the anatomical and physiological characteristics of various parts of the nervous system, the main syndromes of the nervous system are considered. The methods of examining the patient with the pathology of the nervous system have been visually and in detail consecrated. The textbook is intended for students of English-language faculties of medical universities, clinical residents and neurologists.